(untitled) (Journal of Advances and Scholarly Researches in Allied Education, 2018)
Utilization of industrial waste materials in the improvement of problematic soils is a cost efficient and environmental friendly method. It helps in reducing disposal problems caused by the various industrial wastes. However, it is essential to understand the performance of these waste products prior to use. The present paper evaluated the potential of granulated blast furnace slag (GBS) with fly ash to stabilize a soft soil. Soft soil samples were collected from Datala, rural area in Chandrapur district, Maharashtra, India. This soil was classified as CI as per Indian Standard Classification system (ISCS). Different amounts of GBS, i.e. 3, 6, and 9 with different amount of fly ash i.e 3, 6, 9 and 12 were used to stabilize the soft soil. The performance of GBS with fly ash modified soils was evaluated using compaction and california bearing ratio (CBR) test. Based on these performance tests, optimum amount of GBS with fly ash was determined as 3 fly ash + 6 GBS. Reasonable improvement has been observed for unsoaked and soaked CBR value of soils with this optimum amount.